A business model and cost analysis of automated platoon vehicles assisted by the Internet of things. (February 2021) - Chen, Junyan; Chen, Haibo; Gao, Jianbing; Pattinson, Jo-Ann; Quaranta, Romina
Platoon services are being driven by the development of Internet of things, prompting changes in existing businesses and the generation of new businesses. In this paper, a business model and business model canvas related to platoon services are proposed, and the cost analysis of heavy freight transport platoon services from the perspective of platoon leaders and followers is conducted. In addition, the fuel consumption saving brought about by platoon services in freight transport of 28 European Union countries is estimated. The results indicate that the providers of the autonomous driving package, Internet of things devices and the platoon service platform are new stakeholders in the business model. The business model canvas shows the value propositions of platoon services, such as increased traffic efficiency, decreased energy consumption, and the opportunity of involvement in other activities. In addition, the analysis of cost structures for platoon leaders and followers shows that the autonomous driving package has the highest percentage of cost in the first year of a vehicle's lifespan and decreases rapidly in the years that follow. The platoon services ease the financial burden of the leaders due to decreased fuel consumption and income from the leading service, with the highest value up to 4.7%. As for the fuel consumption reductions benefited from platoon services, Germany may have the largest potential of national annual fuel saving, followed by France, Spain and the United Kingdom, while the countries that may benefit the most from fuel savings in international freight transport are Poland and Spain.